Toward a Better Preparation of Student Teachers’ Reading Skill: The SQ3R Strategy with Authentic and Simplified Texts on Reading Literacy and Vocabulary Mastery - Robi Soma; Amirul Mukminin; Noprival Noprival (Intelektual Pustaka Media Utama, 2015)
The purpose of the quantitative study with a factorial experimental approach was to examine the significant increase and difference of students’ achievement in reading literacy and vocabulary mastery after being taught through the SQ3R with authentic texts and simplified texts at one English Study Program Public University in Jambi, Indonesia. The sample of this study was 56 six semester student teachers at one public university in Jambi. To collect the data, pre-test and post-test techniques were used. The result of paired sample t-test showed that there was a significant progress in students’ achievement of reading literacy and vocabulary mastery of both experimental groups. Moreover, the result of independent sample t-test analysis showed that there was no significant difference in students’ achievement of reading literacy and vocabulary mastery between both experimental groups as well as level of achievement. The factorial analysis showed that there was an interaction between the kind of texts and students’ level of achievement both high and low achievers. Implications of findings and suggestions are discussed